AN INVESTIGATION INTO THE LEADERSHIP CHALLENGES THAT CHARACTERISE STATE OWNED ENTERPRISES IN ZIMBABWE: A Case Study of the Zimbabwe Rural Electrification Agency (REA) - Thomas, Bhebhe; Alex, Chikozho; Obert, Sifile; M. Desderio, Chavunduka (IJRDO - Journal of Business Management, 2019)
The study investigated the leadership challenges that characterize State Owned Enterprises (SOEs) in Zimbabwe with specific focus on the Zimbabwe Rural Electrification Agency (REA). Like most State-Owned Enterprises in Zimbabwe and in most countries, REA faced many challenges leading to poor service delivery and huge losses among a plethora of other problems. The study employed a case study approach and questionnaires were administered on 105 respondents. Key informants from selected members from the parent Ministry, REA Board and executive were subject to face-to-face interviews. The study found that some of the leadership problems which led to poor performance at REA included bureaucracy, nepotism, abuse of power, lack of commitment, poor corporate governance practices, lack of accountability, inappropriate leadership styles and poor communication. Employees at REA were generally aware of the vision and mission of the organization. The study found out that inefficiency at REA is partly exacerbated by the fact that it is a monopoly. It was revealed that the organization did not carry out external audits of accounts frequently. The correlation tests showed that there is a relationship between SOE performance and failure to adhere to the principles of good corporate governance. The study recommended that management should be exemplary in their conduct and actively promote employee motivation. The answer could lie in opening REA’s services to competition.